Carta do Cônsul em Cantão para o Ministro Secretario do Estado dos Negocios Estrangeiros, sobre o movimento anti-missionario na China, incluindo Hainan (1891)
This 1891 diplomatic dispatch, dated 23–24 June and originating from the Portuguese Consulate in Canton, documents escalating anti-European and anti-missionary unrest in southern China amid a broader wave of hostility spreading from central regions. The Viceroy of Canton, responding to inflammatory placards and public agitation, requested foreign consulates to suspend missionary activities to prevent violence, while an attempted arson attack on a missionary residence heightened tensions. With no warships present for protection, the consular corps coordinated emergency evacuation plans, designating the British consulate as a rallying point. A separate incident involving Agostinho de Jesus, a man of uncertain origin regarded as Portuguese, aboard the steamer *Honan*—in which he allegedly attacked a Chinese passenger—sparked exaggerated rumours of murder, prompting fears of mob retaliation. The situation was defused by preventing the steamer’s landing and dismissing the individual. The document attributes the wider disturbances not to organised political resistance by the Cau-lau-hui secret society, but to bands of disbanded soldiers and brigands exploiting anti-foreign sentiment to justify plunder. Authorities in Canton responded with repression, imprisoning those criticising Europeans. The anonymous correspondent, likely a Portuguese consular official, urges reinforcement of the naval presence in Chinese waters, arguing that existing forces are inadequate to protect Portuguese interests across Shanghai, Canton, Macau, and Hainan, particularly given the fragile security climate and potential for renewed violence linked to compensation claims.
Keywords: Agostinho de Jesus; Anti-European hostility; Anti-missionary unrest China; Attempted arson missionary residence; British consulate rallying point; Canton Viceroy; Cau-lau-hui not organized resistance; Chinese waters diplomacy; Consular dispatch 1891; Defused maritime conflict; Diplomatic response to violence; Disbanded soldiers brigands; Document historical significance; Emergency evacuation plans; Foreign Consuls Coordination; Honan steamer incident; Hui secret societies; Inflammatory placards; Missionary activity suspension; Portuguese Consulate in Canton; Regional anti-foreign sentiment; Rumors murder mob retaliation; Security measures foreign diplomats; Southern China unrest; Transcription; Unidentified individual report